Placebo effect on progression and regression in NASH: Evidence from a meta‐analysis. Issue 6 (24th January 2022) - Ng, Cheng Han; Xiao, Jieling; Lim, Wen Hui; Chin, Yip Han; Yong, Jie Ning; Tan, Darren Jun Hao; Tay, Phoebe; Syn, Nicholas; Foo, Roger; Chan, Mark; Chew, Nicholas; Tan, Eunice XX; et al.
Abstract: Background and Aims: The evaluation of the natural history of NASH has been limited. Currently, liver biopsy remains the gold standard in the assessment of NASH. Placebo‐controlled trials represent a controlled environment with paired biopsies for the evaluation of NASH. This meta‐analysis thus seeks to quantify the change severity of NASH over time, with patients on placebo arms from randomized controlled trials (RCTs) to examine the natural history of NASH. Methods: A search was conducted to include NASH RCTs with placebo treatment arms. Primary outcomes were (1) the resolution of NASH without worsening of fibrosis, (2) two‐point reduction in NAFLD activity score without worsening of fibrosis, and (3) at least one‐point reduction in fibrosis. Generalized linear mix model was used to estimate pooled proportion and mean differences. Results: This meta‐analysis of 43 RCTs included 2649 placebo‐treated patients. The pooled estimate of NASH resolution and two‐point NAFLD activity score reduction without worsening of fibrosis was 11.65% (95% CI: 7.98‐16.71) and 21.11% (95% CI: 17.24‐25.57). The rate of ≥1 stage reduction and progression of fibrosis was 18.82% (95% CI: 15.65‐22.47) and 22.74% (CI: 19.63‐26.17), respectively. Older age and African American ethnicity was associated with lower NASH resolution rate in placebo‐treated patients. Conclusions: Despite the absence of any pharmacological interventions, a significant proportion of patients in the placebo arm demonstrated improvements in liver histology, highlighting the possibility that NASH is a disease that can not only progress but regress spontaneously over time. Additionally, histologic response in placebo‐treated patients is helpful in future design of phase 2B and phase 3 trials. Abstract : image